Collagenase Chemonucleolysis for Treating Cervical Disc Herniation: An Exploratory, Single-Arm, Open-Label, Multicenter Clinical Trial - Zhijian Wang; Bifa Fan; Lili Gu; Xuexue Zhang; Tao Sun; Hui Liu; Rongchun Li; Likui Wang; Kaiqiang Wang; Shun Li; Yong Ma; Haibo You; et al. (Pain and Therapy)
Abstract Introduction Cervical disc herniation (CDH) is the most common cause of cervical radiculopathy and causes persistent neck pain and neurological deficits. Collagenase chemonucleolysis has been successfully applied to treat lumbar disc herniation, which has a similar pathological mechanism to CDH. However, its application for CDH remains under-researched, and there is an even greater lack of high-quality clinical evidence. This study aims to evaluate the efficacy and safety of collagenase chemonucleolysis for treating CDH. Methods Eligible patients with CDH underwent collagenase chemonucleolysis via anterior cervical intradiscal injection or epidural injection. The primary efficacy endpoint showed an excellent and good rate regarding the Odom criteria, which was not lower than the reference value (≥ 78%) at 6 months postoperatively. The secondary efficacy endpoints were the percentage reduction in Numeric Rating Scale (NRS) and Neck Disability Index (NDI) scores from baseline, which were not lower than the reference values (≥ 40%, ≥ 30%), and improvement in the 36-Item Short Form Health Survey (SF-36) score compared to the preoperative value. The pre- and postoperative CDH index of patients were also compared. Safety endpoints included the incidence of adverse events (AEs) and serious adverse events (SAEs). Results An excellent and good rate regarding the Odom criteria 6 months postoperatively was 90.5% (133/147), which was significantly higher than 78% (P < 0.004, 95% confidence interval 85.7–95.2%). The reduction in NRS and NDI scores exceeded 40% (P < 0.001) and 30% (P < 0.001), respectively. The SF-36 scores at 3 months and 6 months postoperatively were significantly higher than those preoperatively (P < 0.001). A significant difference was observed in the pre- and postoperative CDH index (109.6 ± 119.1 vs. 70.8 ± 74.8, P < 0.001). The incidence of AEs was 22.5% (33/147), of which 97.8% were grade 1–2. No collagenase-related AEs and SAEs occurred. Conclusion Collagenase chemonucleolysis treatment for CDH exhibited favorable efficacy and safety and may be a better choice for patients in whom conservative treatment is ineffective. Trial Registration The trial was registered on www.Chictr.org.cn (ChiCTR2200063043).